Citizens' perception of government responsiveness: building an engaged citizenry. Issue 4 (2nd October 2021) - Novikova, Irina; Liebert, Saltanat
ABSTRACT: Responsiveness is one of the tenets of good governance. In the post-Soviet setting, in which government officials view provision of public services to the population as government largesse, the perception of government responsiveness is particularly important in building active and engaged citizenry. This study explores a potential link between citizen perceptions of local government responsiveness among residents of squatter settlements in the Kyrgyz Republic and citizen-municipal government collaboration. Based on a survey of 914 urban squatter settlers in Bishkek, the article examines how residents of slums perceive the responsiveness of different levels of government in improving their communities' access to basic urban services. Lower level of governance is found to be associated with higher levels of perceived responsiveness. Participation in informal demand-making and self-help activities is positively associated with perceptions of government responsiveness, especially when it comes to the city administration.